2014
DOI: 10.4236/ojog.2014.416139
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Sexual Behavior among Female Adolescents in Onitsha, Nigeria

Abstract: Background: The sexual health indices of the adolescents are very poor. This study ascertained the factors influencing the sexual behaviour among female adolescents in Onitsha, Anambra state, Nigeria. Method: This was a cross sectional design in which a total of 800 female adolescents were selected from secondary schools in the area using multistage sampling method; and also selected from a major market (for those who were not at school) in the same geographical area using cluster sampling technique. Data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 18 publications
2
11
0
Order By: Relevance
“…This may be explained by the collaboration of Ministries of Health and Education in sensitization of students using health workers and the inclusion of sexuality education in school curriculum in Ebonyi State. The finding is consistent with the report of a study conducted among secondary school students in Onitsha, Nigeria [21] and in other developing countries:-Ghana [22], Botswana [20] and Ethiopia [23]. However, contrary to our finding, a study among adolescents in Osun State, Nigeria reported that the most common source of information on contraception was chemist shops [24].…”
Section: Awareness and Knowledge Of Contraceptionsupporting
confidence: 91%
“…This may be explained by the collaboration of Ministries of Health and Education in sensitization of students using health workers and the inclusion of sexuality education in school curriculum in Ebonyi State. The finding is consistent with the report of a study conducted among secondary school students in Onitsha, Nigeria [21] and in other developing countries:-Ghana [22], Botswana [20] and Ethiopia [23]. However, contrary to our finding, a study among adolescents in Osun State, Nigeria reported that the most common source of information on contraception was chemist shops [24].…”
Section: Awareness and Knowledge Of Contraceptionsupporting
confidence: 91%
“…With regards to their various types of impairment, those with hearing disabilities were the majority (52.1%) followed by the visually impaired. In a similar studies conducted in parts of Nigeria among the same population group, it was found that the hearing impairment were also high [15, 16]. These findings were inconsistent with what was reported in the United States of America and in Europe where intellectual disabilities were found to be high [17, 18].…”
Section: Discussionmentioning
confidence: 87%
“…Madise et al (2008) found a correlation between low SES and risky sexual behaviours such as casual sex and multiple partnering (Madise et al, 2007). Reporting on Nigeria, Udigwe et al (2014) found that poor women were more likely to engage in transactional sex relative to those from better-off households. They found that adolescents who experienced these shocks in their households Sexual debut and school completion in South Africa were more prone to debut sexually during the period of the income shock.…”
Section: Conceptualizing Adolescent Sexual Behavioursmentioning
confidence: 99%
“…Dinkelman et al (2008) examined the effect of income shocks related to death, illness and job loss of household providers. Implicit in the understanding of this relationship is that low SES often results in low educational attainment and, by extension, limited earning and economic power (O'Sullivan et al, 2006;Udigwe, 2014): 'These factors will in turn lead to transactional sex in search of income, transgenerational sex or pursuit of multiple sexual partners' (Udigwe et al, 2014, p. 988). Reporting on Nigeria, Udigwe et al (2014) found that poor women were more likely to engage in transactional sex relative to those from better-off households.…”
Section: Conceptualizing Adolescent Sexual Behavioursmentioning
confidence: 99%